2013
DOI: 10.3109/00498254.2012.756992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amlodipine on the pharmacokinetics of tacrolimus in rats

Abstract: 1. The immunosuppressant tacrolimus (TAC) is a substrate of cytochrome P450 3A2 (CYP3A2) and P-glycoprotein (P-gp) in rats. Amlodipine (AML) is an inhibitor of CYP3A2 in rats. We investigated the effect of AML on the pharmacokinetics of TAC in rats. 2. When co-administered with TAC orally or intravenously, AML decreased the oral clearance and raised the blood concentration of TAC in rats, but the T1/2 of TAC was not significantly affected by AML. Upon oral administration of TAC, the effect of 15 mg/kg of AML o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Tacrolimus is a substrate of P-gp product of MDR1 gene, 16,27,28) but it still remains controversial whether the MDR1 SNPs affect tacrolimus pharmacokinetics. 29,30) Our study did not find any significant difference in tacrolimus pharmacokinetic parameters among different MDR1 genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tacrolimus is a substrate of P-gp product of MDR1 gene, 16,27,28) but it still remains controversial whether the MDR1 SNPs affect tacrolimus pharmacokinetics. 29,30) Our study did not find any significant difference in tacrolimus pharmacokinetic parameters among different MDR1 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP3A4*1G mutation allele has higher activity than the CYP3A4*1/*1 wild type. 27) It has been identified that CYP3A4*1G polymorphism was associated with the pharmacokinetics of tacrolimus. 35,36) In our study, CL/F of tacrolimus (5 mg) in CYP3A4*1/*1 genotype subjects (98.5 l/h) was less than that in CYP3A4*1G carriers (162.4 l/h) (p = 0.556) in the single-dose study.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset consisted of 1043 compounds with human f a , ,,,,,,, 125 with rat f a , ,,,,, and 484 compounds with Caco-2 P app ,,,,,,,,,, ,,, and human f a . When multiple permeability values were found for a single compound from more than one source, the geometric mean of the values was used as the point estimate.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Our results show that a higher tacrolimus dose did not result in higher intra-renal tacrolimus concentration. Tacrolimus is a substrate of CYP3A2 enzyme and PGP in rats 124 . The lack of correlation between tacrolimus dose level and its renal tissue concentration requires further investigation in a larger group of animals to elucidate whether it is an artifact of a small sample size, or related to an underlying physiological mechanism such as up-regulation of transporter proteins.…”
Section: Accuracy and Precisionmentioning
confidence: 99%